2017
DOI: 10.14218/jcth.2016.00056
|View full text |Cite
|
Sign up to set email alerts
|

Immune Dysfunction in Cirrhosis

Abstract: Cirrhosis due to any etiology disrupts the homeostatic role of liver in the body. Cirrhosis-associated immune dysfunction leads to alterations in both innate and acquired immunity, due to defects in the local immunity of liver as well as in systemic immunity. Cirrhosis-associated immune dysfunction is a dynamic phenomenon, comprised of both increased systemic inflammation and immunodeficiency, and is responsible for 30% mortality. It also plays an important role in acute as well as chronic decompensation. Immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
123
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(127 citation statements)
references
References 109 publications
3
123
1
Order By: Relevance
“…As a result, prolonged high serum concentration of the drug potentiates acid suppression and may increase a PPI associated side effects [44]. Immune suppressive effects can be more harmful in patients with cirrhosis known to be immunocompromised with a multifactorial state of systemic immune dysfunction [45]. The unnecessarily high dose of the drug further enhances negative effects of PPI.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, prolonged high serum concentration of the drug potentiates acid suppression and may increase a PPI associated side effects [44]. Immune suppressive effects can be more harmful in patients with cirrhosis known to be immunocompromised with a multifactorial state of systemic immune dysfunction [45]. The unnecessarily high dose of the drug further enhances negative effects of PPI.…”
Section: Discussionmentioning
confidence: 99%
“…Nourieta et al demonstrated a broad defect of T cells and hyperactivity of B cells in patients with alcoholic liver disease. Specifically, these patients have circulating IgG and T lymphocytes that recognize epitopes against lipid peroxidation derived antigens and are associated with an increase in hepatic production of proinflammatory cytokines and chemokines.Doi et al reported that memory CD27+ B cells were reduced in the peripheral blood of pa- tients with cirrhosis, independent of etiology, and that this reduction led to impaired TNF-b and IgG production, vaccine hyporesponsiveness and susceptibility to bacterial infection [9].…”
Section: Discussionmentioning
confidence: 99%
“…Cirrhotic patients experience immune dysfunction due to alterations in both innate and acquired immunity including impaired phagocytic activity and lymphocyte derangement . BCAA supplementation in cirrhotic patients restores the phagocytic activity of neutrophils, increases the number of intrahepatic lymphocytes, and augments the natural killer activity of lymphocytes .…”
Section: Branched‐chain Amino Acids and Hepatic Encephalopathymentioning
confidence: 99%